2017
DOI: 10.1016/j.bjpt.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotherapy improves pain and function in older women with knee osteoarthritis: a randomized controlled trial

Abstract: HighlightsElderly women with knee osteoarthritis are at risk of developing limitations physical.Hidrotherapy improves pain, function, muscle power and strength in older women with knee osteoarthritis.Hydrotherapy is likely to be an effective treatment option for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 35 publications
1
63
0
8
Order By: Relevance
“…In general, medications [ 5 , 6 ], psychotherapy [ 7 ], counseling [ 8 ], cognitive behavior therapy [ 9 ], self-care instructions [ 10 , 11 ], and rehabilitation or therapeutic exercises [ 12 , 13 ] are recommended as treatments for FM patients. Underwater walking is a therapeutic exercise that has often been utilized for gait training for patients with painful diseases, such as osteoarthritis [ 14 ], rheumatoid arthritis [ 15 ], arthroplasty [ 16 ], and FM [ 17 – 20 ]. Although the functional activity of antigravity muscles, such as the erector spinae, gluteus maximus, quadriceps, and triceps surae, is required for walking, underwater walking appears to decrease overload on the antigravity muscles.…”
Section: Introductionmentioning
confidence: 99%
“…In general, medications [ 5 , 6 ], psychotherapy [ 7 ], counseling [ 8 ], cognitive behavior therapy [ 9 ], self-care instructions [ 10 , 11 ], and rehabilitation or therapeutic exercises [ 12 , 13 ] are recommended as treatments for FM patients. Underwater walking is a therapeutic exercise that has often been utilized for gait training for patients with painful diseases, such as osteoarthritis [ 14 ], rheumatoid arthritis [ 15 ], arthroplasty [ 16 ], and FM [ 17 – 20 ]. Although the functional activity of antigravity muscles, such as the erector spinae, gluteus maximus, quadriceps, and triceps surae, is required for walking, underwater walking appears to decrease overload on the antigravity muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Water buoyancy causes the patients to move more comfortably and less painfully than on the land. In addition, warm water provides more muscle relaxation and symptom palliation [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…These exercises are generally performed either on the ground or in water. Water-walking has often been utilized as a therapeutic exercise for painful arthritic conditions such as osteoarthritis ( Dias et al, 2017 ) and rheumatoid arthritis ( Bilberg et al, 2005 ). It has been reported that exercise in chest-high warm water decreases pain and improves cognitive function in patients with FM ( Mannerkorpi et al, 2009 ; Segura-Jiménez et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%